Structured illumination microscopy reveals focal adhesions are composed of linear subunits. Issue 5 (May 2015) - Hu, Shiqiong; Tee, Yee‐Han; Kabla, Alexandre; Zaidel‐Bar, Ronen; Bershadsky, Alexander; Hersen, Pascal
<x xml:space="preserve">Abstract</x> The ability to mechanically interact with the extracellular matrix is a fundamental feature of adherent eukaryotic cells. Cell–matrix adhesion in many cell types is mediated by protein complexes called focal adhesions (FAs). Recent progress in super resolution microscopy revealed FAs possess an internal organization, yet such methods do not enable observation of the formation and dynamics of their internal structure in living cells. Here, we combine structured illumination microscopy (SIM) with total internal reflection fluorescence microscopy (TIRF) to show that the proteins inside FA patches are distributed along elongated subunits, typically 300 ± 100 nm wide, separated by 400 ± 100 nm, and individually connected to actin cables. We further show that the formation and dynamics of these linear subunits are intimately linked to radial actin fiber formation and actomyosin contractility. We found FA growth to be the result of nucleation of new linear subunits and their coordinated elongation. Taken together, this study reveals that the basic units of mature focal adhesion are 300‐nm‐wide elongated, dynamic structures. We anticipate this ultrastructure to be relevant to investigation of the function of FAs and their behavior in response to mechanical stress. © 2015 Wiley Periodicals, Inc.